Stabilization of Expansive Soil with Waste Marble Dust and Sugar Cane Molasses (Case of Modjo Town, Ethiopia) - Liben, Taressa (ASTU, 2025)
Foundation soils need to have some desirable properties such as good stiffness, shear strength, volume stability, bearing capacity, etc. If these properties are not satisfied for the required civil engineering projects, should be stabilized with best stabilization method. Expansive soils are known for their high compressibility and low bearing capacity in the fluctuation of saturation level. In this thesis, improvement of expansive soil by adding Waste marble dust and sugar cane molasses through laboratory experiment were performed. The objectives of the thesis are to improve engineering behavior of expansive soil by mixing Waste marble dust and sugar cane molasses. Waste marble dust15%, 20%, 25% and 30%; and sugar cane molasses 4%, 6% and 8% additives added to expansive soil to obtain optimum improvement of engineering behavior of expansive soil. Utilization of waste like marble and sugar cane molasses is an alternative mechanism to protect environmental pollution, health and reduce construction cost. The findings of this thesis reveal that WMD and SCM could be used to stabilize expansive soil stabilize. As the percentage of WMD and SCM increases the engineering properties of expansive soil gets improved. Optimum amount of WMD and SCM that best improves the engineering properties of expansive soil are 25% and 8% respectively.
Keywords: Expansive Soil, Waste marble dust, Sugar Cane Molasses, Soil Modification